Peran Bimbingan Karir Dalam Membantu Siswa SMK Mengambil Keputusan Antara Bekerja Atau Melanjutkan Perguruan Tinggi: Kajian Literatur - Debi Agustin (Ameena Journal, 2026)
Career guidance is one of the core services in school counseling that helps individuals understand themselves and the world of work, enabling them to make wise and well-planned career decisions. Vocational High School (SMK) students in Indonesia are commonly assumed to enter the workforce directly after graduation, yet many of them face a dilemma between starting work and continuing to higher education. This study uses a systematic literature review to examine the role of career guidance in assisting SMK students through this decision-making process. The review covers the conceptual foundations of career guidance, relevant theories (Holland's career personality theory and Super's career development theory), internal and external factors influencing students' career decisions, effective service strategies, and the barriers encountered in implementation. The findings indicate that career decision-making among SMK students is shaped by a complex interaction of personal interests, self-efficacy, and self-concept, alongside family socioeconomic conditions, parental expectations, peer influence, and the quality of school-based career services. Structured, continuous, and contextual career guidance programs, supported by collaboration among counselors, schools, families, and industry, have been shown to significantly improve students' career maturity and readiness. This review underscores the urgency of designing inclusive and context-sensitive career guidance services that accommodate the dual pathway faced by SMK graduates.